Impact of herding behavior, risk perception, and financial literacy on student investment decisions in Palembang - Maureen Marcia Marvin; Catharina Clara; Gustiah Elissia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
College students’ investment decisions are often affected by their financial illiteracy and socio behavior in their environment.